Analisis Yuridis Penegakkan Hukum Pidana Terhadap Berita Hoax di Dalam Masyarakat - Annas Hakim Muzaki Sarwono (CV. Lenggogeni Data Publishing, 2024)
Crime in cyberspace or cyberspace is closely related to the wider development and influence of internet technology in modern human life. The development of the internet in the world is very fast, including in Indonesia. Fake news is processed in such a way as to attract readers. Netizans participate in the comments column to discuss news with the assumption that they can straighten the news through their opinion. Hoaxes and Elections, these two words are an important part of the performance of Indonesian democracy, because both have a connection in voter participation to determine their political choices, especially in an era of democracy which is very prone to divisions. Each political fighter is scrambling to attract the sympathy of the voters by taking advantage of the rapid advancement of technology as a way to attract voters' attention. As in the decision of the South Jakarta District Court Number: 203 / Pid.Sus / 2019 / PN.Jkt.Sel, the defendant Ratna Sarumpaet was sentenced to imprisonment for 2 (two) years because it was legally and convincingly proven guilty of committing a crime of misconduct. Prevention efforts are carried out by various parties in government elements, including the police and other law enforcers. Prevention efforts start from educating the public about the difference between original articles and hoax articles that often appear. Explanation of the types of hoax articles that often appear is also important education for the community to avoid hoaxes that divide the nation. Abstrak Tindak pidana dalam dunia Cyber atau dunia maya terkait erat dengan semakin luasnya perkembangan dan pengaruh teknologi internet dalam kehidupan manusia modern. Perkembangan internet di dunia amatlah pesat termasuk di Indonesia. Pemberitaan palsu diolah sedemikian rupa agar menarik minat pembaca. Para netizan turut serta dalam kolom komentar untuk membahas suatu berita dengan anggapan mereka dapat meluruskan berita tersebut melalui opininya. Hoax dan Pemilu, dua kata ini menjadi bagian penting dalam pergelaran demokrasi Indonesia., sebab keduanya memiliki keterkaitan dalam partisipasi pemilih untuk menentukan pilihan politiknya, khususnya di era demokrasi yang sangat rentan dengan perpecahan. Masing-masing petarung politik berebut menarik simpati para pemilih dengan memanfaatkan kemajuan teknologi yang begitu pesat sebagai salah satu cara untuk menarik perhatian pemilih. Sebagaimana dalam putusan Pengadilan Negeri Jakarta Selatan Nomor: 203/Pid.Sus/2019/PN.Jkt.Sel, terdakwa Ratna Sarumpaet dipidana dengan pidana penjara selama 2 (dua) tahun karena terbukti secara sah dan meyakinkan bersalah melakukan tindak pidana keonaran. Upaya pencegahan dilakukan oleh berbagai pihak dalam elemen pemerintahan, termasuk polisi dan penegak hukum yang lainnya. Upaya pencegahan dimulai dari memberikan edukasi terhadap masyarakat tentang perbedaan antara artikel asli dengan artikel hoax yang sering muncul. Penjelasan jenis-jenis artikel hoax yang sering muncul juga menjadi edukasi penting bagi masyarakat agar terhindar dari hoax-hoax yang memecah belah bangsa. Kata Kunci: Penegakkan Hukum, Tindak Pidana Siber, Berita Palsu